2009
DOI: 10.1021/jp9078629
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Bonding in Fluorinated Nanodiamond

Abstract: We report on a combined investigation of the structure and chemical bonding in fluorinated detonation nanodiamond by means of nuclear magnetic resonance, electron paramagnetic resonance, X-ray photoelectron spectroscopy, and Raman measurements. The results of these methods are found to be consistent with each other and evidence formation of different fluorocarbon groups on the nanodiamond surface, which substitutes for hydrocarbon and hydroxyl groups. The data obtained provide detailed information about the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 59 publications
3
40
1
Order By: Relevance
“…3, spectra 1 and 2) prevented to detect it. The problem was how to simulate [44] and subsequently subtract this broad line to see the spectrum of P1-centers. We have found that fitting of the broad line by the mixed Lorentz + Gauss derivative line (XEPR software) gave good results ( Figure 3, spectra 1' and 2').…”
Section: Methodsmentioning
confidence: 99%
“…3, spectra 1 and 2) prevented to detect it. The problem was how to simulate [44] and subsequently subtract this broad line to see the spectrum of P1-centers. We have found that fitting of the broad line by the mixed Lorentz + Gauss derivative line (XEPR software) gave good results ( Figure 3, spectra 1' and 2').…”
Section: Methodsmentioning
confidence: 99%
“…A possible alternative is the fluorination of the surface using a gas mixture of F 2/ /H 2 at elevated temperatures or using plasma treatment [59]. The presence of fluorine atoms enables for further substitutions with alkaline reagents such as amines and Grignard’s reagents.…”
Section: Synthesis and Functionalization Of Ndsmentioning
confidence: 99%
“…As fluorinated and hydroxylated NDs are experimentally studied [11,12,14], we have proposed several types of NDs, derived from the aforementioned C 197 H 160 nanostructure and coated with F atoms or OH groups. The modified NDs with only one carbon atom functionalized by two groups were used for auxiliary calculations.…”
Section: Polarizability Of Fluorinated and Hydroxylated Ndsmentioning
confidence: 99%
“…This causes diversity of their applications: as additives in polymer composites [4], platforms for drug delivery [5], fluorescent markers for biomedical applications [6], materials for solar cells [7] and electronic devices (see also reviews, considered on the applications [2,3,8,9]). In addition to the production strategies, physicochemical properties of NDs may be tuned by surface modifications [10][11][12][13][14][15][16][17], so NDs are chemically functionalized in many ways by coating with hydrogen [11,14,16], fluorine atoms [11,12], or hydroxyl groups [14,17]. Another way of changing the ND properties comes from the inside, viz.…”
Section: Introductionmentioning
confidence: 99%